The Effect of Compensation and Empowerment on Teacher and Staff’s Loyalty - Nur Asni Gani; Anita Kusumaningrum; Nurul Kusuma Dewi; Ari Kartiko; Ainun Nisai Anuha (AL-ISHLAH: Jurnal Pendidikan, 2022)
The goal of this study is to figure out how compensation affects loyalty by giving people more power. It does this by using a quantitative method called SEM (Structural Equation Modeling) analysis with the help of the SPSS 23 and Amos 24 programmes. The research instrument was put through tests to see if it was valid and if it could be trusted. In this study, 125 people answered a questionnaire. The data was collected using a saturated sampling method, meaning the whole population was used as a sample. Based on the results of this study, we know that the value of cr in H1 is 4.215.2. This means that it has significant results, which means that compensation variables significantly affect loyalty. Since H2 has a cr value of 2.860 2, we know that the empowerment variables have a big effect on loyalty. H3 has a value that says the total effect of pay on loyalty through empowerment is greater than the direct effect. This means that empowerment is an intervening variable that will help make teachers and staff more loyal.